The Russian drug glyciphon, a representative of organophosphorus epoxides, for the treatment of basal cell carcinoma – clinical and experimental studies - L. N. Zalyalyutdinova; R. S. Garaev (Опухоли головы и шеи)
The review deals with the results of clinical and experimental studies of the original Russian drug glyciphon used to treat basal cell carcinoma (BCC). Glyciphon is diglycidyl ether of methylphosphonic acid, which has been synthesized at the A. E. Arbuzov Institute of Organic and Physical Chemistry, Kazan Research Center, Russian Academy of Sciences, belongs to a class of organophosphors epoxides. The drug has been experimentally tested by Kazan scientists who revealed the selectivity of its antiblastoma activity, relatively low toxicity, and high safety when it was used long. The antiproliferatve activity of glyciphon in inhibiting DNA synthesis, retarding all mitotic phases, and blocking the entry of cells into S and M phases plays an important role in its mechanism of antiblastoma action. Glyciphon ointment 30 % is effective in the treatment of primary BCC (solitary tumors and polyneoplasms) and its recurrences after radiation and surgery in the absence of a side skin resorption effect. It may be successfully used to treat BCC that are refractory to radiotherapy and surgical dissection and to detect latent foci of multiple BCC. The ointment is registered as an agent for the treatment of Stage I squamous cell carcinoma, as well as basaliomas (including recurrences after surgery and radiotherapy), Bowen,s disease, senile keratosis. Glyciphon is manufactured by OAO “Tatchempharmpreparaty” (Kazan) (as 30 % ointment from the substance made by the affiliate of the A. E. Arbuzov Institute of Organic and Physical Chemistry, Kazan Research Center, Russian Academy of Sciences.